PEMBELAJARAN BERKEBUN UNTUK ANAK USIA DINI DI TK WIJAYA KUSUMAH TASIKMALAYA - Rika puspita; Taopik Rahman; Gilar Gandana (LPPM Universitas Cipta Mandiri, 2024)
Gardening learning has become an integral part of early childhood education to develop practical skillsand broaden their understanding of nature. This research aims to evaluate the planning andimplementation process of gardening learning at Wijaya Kusumah Kindergarten, Tasikmalaya City andanalyze the benefits that children obtain from these activities. The research method used is a qualitativedescriptive study obtained from interviews, observations and documentation studies. The researchresults show that the planning of gardening lessons involves educators and school principals, while stillbeing guided by the 2013 Curriculum. Gardening activities are carried out by involving children inplanting pak choy vegetable plants using direct soil and sowing seeds. Children's enthusiasm forgardening activities is high, although some are initially afraid. The teacher's role is very important inproviding support and understanding so that all children can participate in gardening activities well.The benefits that children gain from learning to garden include improving psychomotor skills, patience,responsibility, as well as developing emotions and empathy for the environment. Assessments arecarried out using a checklist assessment format that covers various aspects of child development, andthe reflection process helps children understand and evaluate their experiences. This research providesa comprehensive picture of the implementation and benefits of gardening learning at Wijaya KusumahKindergarten.